2022
DOI: 10.1371/journal.pone.0263280
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic evaluation of biochemical and crimp properties of knee joint ligaments and patellar tendon

Abstract: Knee ligaments and tendons play an important role in stabilizing and controlling the motions of the knee. Injuries to the ligaments can lead to abnormal mechanical loading of the other supporting tissues (e.g., cartilage and meniscus) and even osteoarthritis. While the condition of knee ligaments can be examined during arthroscopic repair procedures, the arthroscopic evaluation suffers from subjectivity and poor repeatability. Near infrared spectroscopy (NIRS) is capable of non-destructively quantifying the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In this work, this dependence has been taken into account by adding polynomial features of order 2-3 to the original dataset, which was then used for the development of ML models (table 2). A number of papers use linear methods to construct regressors and classifiers [12,25,31,34,46,62,76]. This approach can potentially be improved by methods that take into account the non-linearity of the feature dependence on the target variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, this dependence has been taken into account by adding polynomial features of order 2-3 to the original dataset, which was then used for the development of ML models (table 2). A number of papers use linear methods to construct regressors and classifiers [12,25,31,34,46,62,76]. This approach can potentially be improved by methods that take into account the non-linearity of the feature dependence on the target variable.…”
Section: Discussionmentioning
confidence: 99%
“…(4) To obtain reflectance spectra R(λ), the absorption and scattering spectra of the first and second layers were calculated [22,40,41,45]. Since it has been experimentally shown that the wide wavelength range of 800-2000 nm is more informative for analysing cartilage degradation [26,30,46,47], the spectral range used in this study was selected to be 800-1700 nm. The spectra were simulated for source to detector distances of 0.5 and 2 mm, as different configurations of the probe allow a signal to be collected from different depths [35], presumably providing the information needed to determine layer thickness and water concentration from the detected spectra.…”
Section: Simulation Of Diffuse Reflectance Spectramentioning
confidence: 99%
“…It should be mentioned that NIRS has been used in many medical and biological fields, including tissue oxygenation monitoring (central nervous system and somatic tissue), biological fluids and solutions composition analysis in addition to molecular structure and interaction analysis. Recent literature shows an increase in published studies describing the use of NIRS to characterize the optical parameters of human tissue, including fibrous tissue like ligaments and tendons, and to estimate their mechanical properties [43,44]. In an experimental study, Torniainen et al showed that NIRS can estimate the biomechanical properties of knee ligaments and patellar tendons [44].…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 99%
“…Recent literature shows an increase in published studies describing the use of NIRS to characterize the optical parameters of human tissue, including fibrous tissue like ligaments and tendons, and to estimate their mechanical properties [43,44]. In an experimental study, Torniainen et al showed that NIRS can estimate the biomechanical properties of knee ligaments and patellar tendons [44]. In another experimental study of a rat induced-knee osteoarthritis model, Afara et al demonstrated that NIRS data and spectral feedbacks enabled the separation of the cartilage samples relative to the severity of osteoarthritis with significant correlation between NIRS findings and the histologic Mankin score [45].…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 99%